PEMBINAAN ROHANI DAN MENTAL TERHADAP DISIPLIN DAN KINERJA PERSONIL SAT BRIMOB POLDA BENGKULU - Iran Tanoki (Manthiq, 2018)
This study aims to determine whether there is influence of spiritual and mental guidance on personnel discipline Satrial Brimob Police Bengkulu. In the context of this study the variables are discipline and performance as dependent on spiritual and mental guidance variables as independent. This research method using quantitative method by using simple regression analysis. This analysis is used to determine whether there is influence of spiritual and mental guidance to discipline and performance of personnel of Brimob Police Bengkulu and to know the amount of influence of spiritual and mental guid- ance to discipline and performance of personnel of Brimob Police Bengkulu. The results of this study indicate that the activ- ity of spiritual and mental guidance in Sat Brimob Bengkulu Police there is an influence on the discipline and performance personnel Sat Brimob Polda Bengkulu. The amount of influence of spiritual and mental guidance (X1) to the discipline (Y1) can be inferred from the calculation of SPSS Version Windows 17.0 determination coefficient shows R Square of 0.243. This explains the level of influence of spiritual and mental guidance on the discipline of Brimob Police Unit Bengkulu personnel in 2018 is 24.3%, while the remaining 75.7% is influenced by other variables besides discipline variables, while the magnitude of spiritual and mental development (X1) performance (Y2) can be concluded from the calculation of SPSS Version Windows17.0 determination coefficient shows R Square of 0.113. This explains the level of influence of spiritual and mental guidance on the performance of Brimob Police Unit personnel Bengkulu 2018 is 11.3%, while the remaining 88.7% influenced by other variables that are not in this study.